Suggesting a Model for Applying Digital Engineering to Lean Project Construction - رنا مـيّا (Latakia University Journal -Engineering Sciences Series, 2022)
Large projects face the risk of an overwhelming amount of unmanageable information and consequently the inability to control the construction process to achieve project objectives. Many advanced companies are currently exploring digitization strategies, including the introduction of DE digital engineering, which enables people to easily model, use and share reliable data to improve decision-making and results for a project or organization, as DE provides a common digital language to coordinate and exchange information across all Stages of the value chain and help reduce waste through the flow of knowledge and information throughout all stages of the project. In the research, we analyzed the current status of the project implementation mechanism in case studies for both the design and implementation stages, where it was found that there is a large percentage of waste and waste of time and effort. The research concluded by proposing a model for using digital engineering to lean construction of projects, that focuses on harnessing the real potential of the construction industry. The model includes the creation of a platform for multiple applications that include digital products and allows digital communication using digital models and the platform allows control of the huge multi-site construction projects and projects.